Pengaruh Leverage terhadap Financial Performance Properti & Real estate di Indonesia (2020–2024): Peran Moderasi Financial distress - Rahma Yuli Ananda; Usman Usman; Ida Farida; Fakhmi Zakaria (Jurnal Ilmiah Global Education, 2026)
This study examines the effect of financial leverage on financial performance in property and Real estate companies listed on the Indonesia Stock Exchange, and whether financial distress modifies that effect. The objective is to  determine whether higher leverage reduces financial performance and  whether financial distress strengthens or weakens that relationship. We use a quantitative panel regression on 68 firms observed between 2020 and 2024. Outliers were screened using the interquartile range and an indicator saturation procedure implemented in EViews 13, yielding 249 usable  observations. Financial leverage is measured by the debt-to-asset ratio, firm  performance by Return on Assets (ROA) and Return on Equity (ROE), and  financial distress by a bankruptcy-risk score (Altman Z-Score). Results show  that higher debt-to-asset ratios significantly reduce both ROA and ROE.  Financial distress does not have a significant direct effect on performance,  but the combined effect of leverage and distress is positive and significant,  indicating that distress tends to weaken rather than amplify the negative  impact of leverage. The findings suggest that firms under financial pressure  often adopt restructuring or efficiency measures that mitigate leverage’s  adverse effects. The study concludes that property firms should manage  leverage carefully and address distress proactively through timely  restructuring and operational improvements to preserve profitability and  long-term viability.